From Mustahik to Muzakki: A Study on The Utilization of Zakat Funds For The Creation and Development of Productives Small Businesses in Lazismu Solo - Zulkarnain Zulkarnain; Farkhani Farkhani (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2021)
The purpose of this research is to see the utilization of zakat funds collected and managed by Lazismu Solo, whether it succeeds in converting mustahik into muzaki or obtaining better than expected results. This field research employs qualitative analysis methods, with data collection techniques through in-depth interviews and field observations. This result shows that the ZIS (Zakat, Infaq, and Alms) fund utilization program to convert mustahik into muzakki seen from the side of program implementation’s effectiveness and efficiency could be considered successful even though it has not been ideal yet in converting mustahik into muzaki. This success has only led to the mustahik becoming an independent Muslim and regardless of their initial status as a mustahik. In the future, this program must continue to be improved until it actually transforms mustahik into muzakki to become one of the ways to eradicate poverty.